2006
DOI: 10.1073/pnas.0605440103
|View full text |Cite
|
Sign up to set email alerts
|

The housekeeping dipeptide permease is the Escherichia coli heme transporter and functions with two optional peptide binding proteins

Abstract: Heme, a major iron source, is transported through the outer membrane of Gram-negative bacteria by specific heme͞hemopro-tein receptors and through the inner membrane by heme-specific, periplasmic, binding protein-dependent, ATP-binding cassette permeases. Escherichia coli K12 does not use exogenous heme, and no heme uptake genes have been identified. Nevertheless, a recombinant E. coli strain expressing just one foreign heme outer membrane receptor can use exogenous heme as an iron source. This result suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
122
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(128 citation statements)
references
References 42 publications
4
122
2
Order By: Relevance
“…Thus, Hmox1 may fulfill cytoprotective effects in Salmonella-infected phagocytes. Nevertheless, an induction of Hmox1 is also invariably associated with a reduction in the haem-associated iron pool [46], a mechanism which may contribute to the withholding of iron from internalized bacteria, some of which may be able to utilize haem molecules as an iron source via specific acquisition systems [47,48]. Given that the incorporation of freshly imported radioactive iron into ferritin multimers was markedly reduced upon addition of IFN-c (Fig.…”
mentioning
confidence: 99%
“…Thus, Hmox1 may fulfill cytoprotective effects in Salmonella-infected phagocytes. Nevertheless, an induction of Hmox1 is also invariably associated with a reduction in the haem-associated iron pool [46], a mechanism which may contribute to the withholding of iron from internalized bacteria, some of which may be able to utilize haem molecules as an iron source via specific acquisition systems [47,48]. Given that the incorporation of freshly imported radioactive iron into ferritin multimers was markedly reduced upon addition of IFN-c (Fig.…”
mentioning
confidence: 99%
“…POP3 (araD139 ⌬lacU169 rpsL relA thi) and POP3 hemA were obtained from a laboratory collection. FB827 dppF::Tn5 has been described previously (9). S. marcescens DB11 was described by Kurz et al (7) and was a gift from J. Ewbank.…”
Section: Methodsmentioning
confidence: 99%
“…The dipeptide AA has a strong affinity for DppA (19), and the tripeptide PFK is transported by MppA-OppBCDF permease (14). In previous work we showed that a combination of these two peptides inhibits heme utilization via the Dpp permease (9). We thus tested whether such competition also occurs via the HemTUV permease.…”
Section: S Marcescens Db11mentioning
confidence: 99%
See 2 more Smart Citations